Sleep and mental status as key factors to asthenopia in Chinese adults - Na Lin; Xin Chen; Xiao-Tian Wu; Fu-Yue Tian; Mao-Yuan Yang; Yong-Shun Liu; Fan Lyu; Ru-Zhi Deng (International Journal of Ophthalmology)
AIM: To investigate the occurrence of eye asthenopia in Chinese adults and pinpoint the factors contributing to it using a 17-item Asthenopia Survey Questionnaire (ASQ-17). METHODS: A total of 2509 Chinese adults aged 18 and above from 30 regions in China participated in a cross-sectional online survey in February 2020. The survey utilized the ASQ-17, which had been proven reliable and validated for assessing asthenopia-related symptoms experienced in the past two weeks among the Chinese population. Data on demographics and living conditions, including age, gender, humidity, air quality in their residential areas, frequency of heightened anxiety or depression, daily duration of near vision activity, sleep duration, sleep quality, and history of eye surgery, were collected. Principal component analysis and multivariate logistic regression were employed to identify independent factors associated with asthenopia. RESULTS: Out of the 2502 participants, with an average age of 31±8y included in the analysis, asthenopia was prevalent in 35.2% of cases. Multivariate analysis revealed that the most influential risk factor was poor sleep and mental well-being, which encompassed shorter daily sleep duration, lower sleep quality, and more frequent feelings of heightened anxiety or depression [odds ratio (OR): 2.07, 95% confidence interval (CI): 1.88–2.29, P<0.001]. This was followed by each additional 2h of daily near vision activity relative to 4h (OR: 1.33, 95%CI: 1.21–1.45, P<0.001), and lower humidity and worse air quality in the residential area (OR: 1.10, 95%CI: 1.02–1.21, P=0.019). CONCLUSION: Asthenopia is a common issue among Chinese adults, and preventative measures should focus on improving sleep and mental well-being. Further research targeting physiological exposure, different age groups or longitudinal studies to establish causality are needed to explore the role of sleep and mental status as an influencing factor.